Brethren in adversity. Bishop George Bell, the Church of England and the crisis of German Protestantism, 1933-1939. Edited by Andrew Chandler. (Church of England Record Society, 4.) Pp. viii+188 incl. frontispiece. Woodbridge: Boydell Press (for the Church of England Record Society), 1997. £35. 0 85115 692 4; 1351 3087 - Railton, Nick (The journal of ecclesiastical history, 1998)
Brethren in adversity. Bishop George Bell, the Church of England and the crisis of German Protestantism, 1933-1939. Edited by Andrew Chandler. (Church of England Record Society, 4.) Pp. viii+188 incl. frontispiece. Woodbridge: Boydell Press (for the Church of England Record Society), 1997. £35. 0 85115 692 4; 1351 3087 - Volume 49 Issue 3